Sistem Pendukung Keputusan Menggunakan Metode Simple Additive Weighting (Saw) Untuk Menentukan Karyawan Terbaik Pada Dealer Motor Berbasis Web - EFIRIYANTO, BAMBANG; , Aris Rakhmadi, S.T., M. Eng (2016)
Company affect is human resources management (HR) many aspects of determining success of the work company. The one most important in human resources management an enterprise the best selection employees to boost employee morale and dedication in improving performance. But, the fact Dealer Kondang Motor still not optimal in election of the best employees, it's caused the unavailability by media processing employee assessment and advise on the best selection employees. Dealer Kondang Motor in selecting the best employees Decision Support System can adjust to optimize . This research purposes is to produce the best employee information more quickly and accurately based on the needs Kondang Motor Dealer. Decision Support System is part of a computer-based information system including a knowledge-based system or knowledge management is used to support decision making in organization or company. The method used is Simple Additive Weighting (SAW), calculation method is to use results of the greatest value will be chosen as the best alternative, calculation would be appropriate if the selected alternative meets criteria predefined. the best selection Decision support system of employees was developed using programming language PHP (Hypertext Processor Files), as well as database server MySQL. This study has shown that the ranking of the best employees with the highest 0.79 and lowest values 0.58.